Plant bioresource dependency and climate perspectives in tropical forests of the Eastern Himalaya - Sumant, Sweeta; Baidya, Shilpa; Singha, Dipshikha; Thakur, Bijay; Bhuyan, Anubhav; Hazarika, Nayan Jyoti; Gogoi, Nirmali; Prakash, Amit; Devi, Ashalata (Ethnobotany Research and Applications, 2025)
Background: The Indian Himalayan Region harbours significant plant bioresources that are essential for species’ survival. These plants provide food, medicine, and economic support while preserving cultural heritage and ecological sustainability. The present study investigates the dependency of local communities on forest plant bioresources, the transmission of ethnobotanical knowledge, and the impacts of climate change on resource availability. Methods: A comprehensive structured questionnaire survey was carried out in 86 households in the Soraipung range using a stratified random sampling method. Data relating to ethnobotanical plants and their socio-economic characteristics were collected over 12 months from September 2021 to August 2022. The informant consensus factor (Fic) was calculated to assess the uniformity of ethnomedicinal plant use across ailment categories. The plant species were identified using relevant literature, the necessary data were collected. Results: It was found that the local people used a total of 80 plants of ethnobotanical importance available in the forest. Among these, 65 species were identified as edible and economically valuable plants, and 44 species have medicinal values. Notably, 25 plants were classified as having edible, economical and medicinal properties. These plants were found to be utilized either for their own consumption and/or commercial purposes. Conclusions: This study has highlighted the significance of preserving ethnobotanical knowledge of available plant bioresources. It also emphasizes the need for further research to provide insights into traditional knowledge to support livelihoods and resilience in the face of climate change. Keywords: Bioresources, Climate change, Ethnobotanical, Forests, Livelihood, Traditional Knowledge.